A solvent-free polyurethane fiber composite material and a method for preparing the same

CN122978692APending Publication Date: 2026-10-27ZHEJIANG HEXIN NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611463370.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是,这种将动态共价键均匀分布于整个基体网络中的设计存在以下问题:一方面,主体承载网络处于动态化状态,在循环热压过程中网络的交联密度和力学性能可能发生衰减,影响承载能力的保持;另一方面,纤维与基体之间的界面同样受到动态网络的影响,界面传力的稳定性难以保证,循环热压后界面脱粘风险显著增加

Benefits of technology

本发明的一种无溶剂聚氨酯纤维复合材料及其制备方法,通过界面动态键与主体稳定网络的协同设计,在保持主体聚氨酯基体高承载性能的条件下,赋予纤维邻近界面热响应的可重塑性,实现了复合材料性能与可加工性的统一;通过分步定量控制界面化学结构,确保了产品性能的稳定性和可重复性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978692A_ABST
    Figure CN122978692A_ABST
Patent Text Reader

Abstract

The present application provides a kind of solventless polyurethane fiber composite material and preparation method thereof.The composite material includes inorganic fiber, epoxy silane layer and polyurethane matrix;Epoxy silane layer includes first ring-opening linking group and second ring-opening linking group, bis (2-hydroxyethyl) disulfide is covalently connected with epoxy silane layer by first ring-opening linking group, and polycaprolactone diol is covalently connected with epoxy silane layer by second ring-opening linking group;Bis (2-hydroxyethyl) disulfide and polycaprolactone diol can participate in the reaction of hydroxyl group after anchoring and react with isocyanate group in solventless polyurethane reaction system to form urethane bond;In addition to bis (2-hydroxyethyl) disulfide covalently anchored in epoxy silane layer in advance, solventless polyurethane reaction system does not contain free disulfide bond chain extender and disulfide bond crosslinking agent.The present application endows the composite material with heat-pressing restyling ability while maintaining high bearing performance and interface durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyurethane composite material manufacturing technology, specifically to a solvent-free polyurethane fiber composite material and its preparation method. Background Technology

[0002] Fiber-reinforced polyurethane composites have wide applications in automotive structural components, rail transit interiors, wind turbine blades, and building formwork. The quality of the interfacial bonding between the inorganic fibers and the polyurethane matrix directly determines the effective load transfer efficiency from the matrix to the fibers, thus affecting the overall mechanical properties, durability, and service life of the composite material.

[0003] In existing technologies, to improve the interfacial bonding strength between inorganic fibers and organic matrices, silane coupling agents are typically used to modify the surface of inorganic fibers. For example, silane coupling agents containing amino, mercapto, or epoxy groups are used to form an organic functional layer on the surface of inorganic fibers, which then connects to the polyurethane matrix through chemical reactions or physical entanglement. Based on this, impregnating the fiber reinforcement with isocyanate-terminated prepolymers and forming the polyurethane matrix through polyol chain extension and crosslinking reactions has become a conventional technical route for preparing fiber-reinforced polyurethane composites.

[0004] However, with increasingly stringent requirements for the recyclability and repairability of composite materials, how to maintain the high load-bearing capacity of composite materials while endowing them with thermosetting capabilities has become an important research direction in this field. For the thermosetting modification of cross-linked polyurethane, existing technologies typically involve uniformly dispersing diols containing disulfide bonds as chain extenders or cross-linking agents into the main polyurethane network structure. This approach allows the entire main network to undergo thermally activated dynamic covalent bond exchange reactions under heating conditions, thereby enabling the reprocessing and reshaping of the material. However, this design, which uniformly distributes dynamic covalent bonds throughout the entire matrix network, has the following problems: On the one hand, the main load-bearing network is in a dynamic state, and the cross-linking density and mechanical properties of the network may decay during cyclic hot pressing, affecting the maintenance of load-bearing capacity; on the other hand, the interface between the fiber and the matrix is ​​also affected by the dynamic network, making it difficult to guarantee the stability of interfacial force transmission, and significantly increasing the risk of interfacial debonding after cyclic hot pressing.

[0005] Furthermore, some technologies utilize silane coupling agents containing sulfur bonds for the bonding modification of polyurethane and inorganic surfaces, or directly composite polyurethane containing disulfide bonds with inorganic materials. However, these technical solutions fail to address the following issues: solely setting up sulfur-bonded interfacial connections or using soft-segment polyols as interfacial modifiers cannot simultaneously define the spatial distribution and functional division between dynamic linking units, movable chain segments, and the main supporting network. Nor can they provide corresponding methods for metering and controlling interfacial reactions or criteria for determining the endpoint of continuous manufacturing. Existing technologies cannot achieve the construction of thermally responsive dynamic connections only in local interfacial regions adjacent to fibers, while maintaining the chemical stability and mechanical reliability of the main supporting network, without introducing a disulfide bond dynamic network into the main polyurethane network.

[0006] Therefore, there is an urgent need in this field for a novel solvent-free polyurethane fiber composite material and its preparation method. This composite material can achieve hot pressing and reshaping through the local interface near the fiber without introducing a disulfide bond dynamic network into the main polyurethane, and maintain stable interfacial force transmission capacity and main load-bearing performance after cyclic hot pressing. Summary of the Invention

[0007] Based on the above background, the purpose of this invention is to provide a solvent-free polyurethane fiber composite material and its preparation method, which achieves synergy between the thermal response dynamic connection of the fiber's adjacent local interface and the chemical stability of the main load-bearing network, thereby endowing the composite material with the ability to be hot-pressed and reshaped while maintaining high load-bearing performance and interface durability.

[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: A solvent-free polyurethane fiber composite material includes inorganic fibers, an epoxy silane layer formed on the surface of the inorganic fibers, and a polyurethane matrix formed using a solvent-free polyurethane reaction system. The epoxy silane layer includes a first ring-opening linking group and a second ring-opening linking group formed by ring-opening different epoxy groups respectively. Bis(2-hydroxyethyl) disulfide is covalently linked to the epoxy silane layer through the first ring-opening linking group, and polycaprolactone diol is covalently linked to the epoxy silane layer through the second ring-opening linking group. The hydroxyl groups of the bis(2-hydroxyethyl) disulfide and the polycaprolactone diol, after anchoring, can react with the isocyanate groups in the solvent-free polyurethane reaction system to form urethane bonds, thereby covalently linking the epoxy silane layer to the polyurethane matrix. Except for the bis(2-hydroxyethyl) disulfide pre-covalently anchored to the epoxy silane layer, the solvent-free polyurethane reaction system does not contain free disulfide chain extenders and disulfide crosslinking agents.

[0009] Preferably, the inorganic fiber is glass fiber or basalt fiber, and the inorganic fiber is in the form of chopped fiber mat, continuous fiber fabric or unidirectional fiber layup.

[0010] Preferably, the epoxy silane layer is formed by hydrolyzing 3-glycidyl etheroxypropyltrimethoxysilane and condensing it with hydroxyl groups on the surface of the inorganic fiber.

[0011] Preferably, the number average molecular weight of the polycaprolactone diol is 1000-2000 g / mol, and the inorganic fiber accounts for 45%-65% of the mass fraction of the solvent-free polyurethane fiber composite material.

[0012] A method for preparing the above-mentioned solvent-free polyurethane fiber composite material, the method comprising the following steps: S1. Dry the inorganic fiber to form an epoxy silane layer on its surface, and measure the initial amount of reactive epoxy groups E0 based on the initial mass of the initially dried inorganic fiber. S2. React bis(2-hydroxyethyl) disulfide with some of the epoxy groups to remove unreacted bis(2-hydroxyethyl) disulfide and measure the remaining epoxy group amount E1; then react polycaprolactone diol with some of the epoxy groups that have not yet reacted after the first stage to remove unreacted polycaprolactone diol and measure the remaining epoxy group amount E2. E0, E1 and E2 are determined using the same method and expressed according to the same mass standard. S3. The inorganic fibers treated in step S2 are brought into contact with a solvent-free polyurethane reaction system containing isocyanate-terminated polyurethane prepolymer and matrix polyol, so that the hydroxyl groups of the matrix polyol and the hydroxyl groups that can participate in the reaction at the interface react with the isocyanate groups to form a polyurethane matrix covalently linked to the epoxy silane layer; except for the pre-anchored bis(2-hydroxyethyl) disulfide, no free disulfide chain extender and disulfide crosslinker are added to the solvent-free polyurethane reaction system.

[0013] Preferably, in step S1, the inorganic fibers are dried at 105-120℃ for 2-4 hours; the inorganic fibers are treated with a 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate with a mass fraction of 0.5%-2.0% and a pH of 4.0-5.0, and after removing excess hydrolysate, they are pre-dried and heat-cured.

[0014] Preferably, in step S2, the apparent conversion rate of the epoxy groups in the first stage, calculated according to formula xH=(E0-E1) / E0, is 0.10-0.25; and the apparent conversion rate of the epoxy groups in the second stage, calculated according to formula xP=(E1-E2) / E0, is 0.05-0.15, when the polycaprolactone diol reacts with the unreacted epoxy groups after the first stage.

[0015] Preferably, in step S2, the bis(2-hydroxyethyl) disulfide is reacted in a dry, inert atmosphere at 60-85°C for 2-8 hours; the polycaprolactone diol is reacted in a dry, inert atmosphere at 80-110°C for 4-12 hours; at least one reaction stage is carried out in the presence of an epoxy ring-opening catalyst, wherein the epoxy ring-opening catalyst is 1-methylimidazolium or tetrabutylammonium bromide.

[0016] Preferably, in step S3, the total hydroxyl equivalent OHt is the sum of the hydroxyl equivalent of the matrix polyol and the measured interfacial hydroxyl equivalent that can participate in the reaction, the total isocyanate equivalent is NCOt, and the NCOt / OHt ratio is 1.02-1.10; the inorganic fiber and the solvent-free polyurethane reaction system are impregnated at 60-80°C and cured at 80-110°C for 2-8 hours.

[0017] Preferably, after the polyurethane matrix is ​​formed and cured in step S3, the obtained solvent-free polyurethane fiber composite material is heated and pressurized at 130-160°C and 1-5MPa for 5-30 minutes, and then cooled to no higher than 60°C under the condition of maintaining external pressure constraint before depressurization.

[0018] Compared with the prior art, the present invention has the following advantages: The present invention discloses a solvent-free polyurethane fiber composite material and its preparation method. Through the synergistic design of interfacial dynamic bonds and the main stable network, the fiber is endowed with remodelable thermal response at the adjacent interface while maintaining the high load-bearing capacity of the main polyurethane matrix, thus achieving a unity of composite material performance and processability. By stepwise quantitative control of the interfacial chemical structure, the stability and repeatability of product performance are ensured. This invention constructs an interfacial structure with a clear spatial division of labor by introducing two functional molecules, bis(2-hydroxyethyl) disulfide and polycaprolactone diol, onto an epoxy-based silane layer. The bis(2-hydroxyethyl) disulfide contains disulfide bonds, endowing the interfacial region with dynamic covalent bond exchange capacity that is thermally responsive; polycaprolactone diol, as a flexible long-chain polyol, provides segmental mobility and stress relaxation capabilities to the interfacial region. These two functional molecules are anchored to the epoxy-based silane layer through different epoxy ring-opening reactions, avoiding mutual interference between functional groups. This invention achieves quantitative control over the degree of apparent epoxy group consumption at the interface through stepwise reaction and quantitative determination of the amount of residual epoxy groups. In the first stage, bis(2-hydroxyethyl) disulfide reacts with some of the epoxy groups; in the second stage, polycaprolactone diol reacts with the remaining epoxy groups. The amount of residual epoxy groups is determined stepwise, and the immobilization of the two types of functional molecules is cross-confirmed by elemental analysis, infrared spectroscopy, extraction and washing, and interfacial hydroxyl group determination, providing a quantitative basis for subsequent polyurethane matrix formulation design. The present invention pre-anchors bis(2-hydroxyethyl) disulfide at the interface, providing dynamic covalent bonds in the local area of ​​the interface. This allows disulfide bond exchange reactions to occur near the fiber interface under heating and pressurization conditions, thereby enabling reshaping operations such as fiber orientation adjustment, local densification, or shape correction. Since the main polyurethane matrix does not contain free disulfide chain extenders and disulfide crosslinking agents, the disulfide bond structure is not uniformly introduced into the bulk polyurethane network as a dynamic structural unit. This helps to reduce the dynamic rearrangement of the main polyurethane network during hot pressing, thus maintaining the load-bearing capacity of the main matrix. In addition, the introduction of polycaprolactone diol not only provides flexible connections, but its long-chain structure also effectively increases the entanglement density of the interface region. Working synergistically with the bis(2-hydroxyethyl) disulfide, it maintains the physical entanglement and mechanical interlocking of the interface region during dynamic bond exchange, avoiding slippage failure that may occur at purely dynamic covalent interfaces. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0020] Figure 1 This is a schematic flowchart of a method for preparing a solvent-free polyurethane fiber composite material according to the present invention; Figure 2 These are FTIR spectra of the fiber surface at different treatment stages in Embodiment 1 of the present invention; Figure 3 This is the XPS S2p high-resolution spectrum of the fiber surface in Embodiment 1 of the present invention; Figure 4 This is a comparison chart of the DMA temperature scan curves of Embodiment 1 and Comparative Example 3 of the present invention; Figure 5 This is a comparison diagram of the constant strain stress relaxation curves at 145 °C for Embodiment 1, Comparative Example 2, and Comparative Example 3 of the present invention. Detailed Implementation

[0021] The technical solution of the present invention will be further described in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications and / or alterations made to the present invention will fall within the protection scope of the present invention.

[0022] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art. Unless otherwise specified, the components or equipment in the following embodiments are general standard parts or components known to those skilled in the art, and their structures and principles can be learned by those skilled in the art through technical manuals or conventional experimental methods.

[0023] Example 1 This embodiment provides a solvent-free polyurethane fiber composite material and its preparation method, such as... Figure 1 As shown, the specific steps of this method are as follows.

[0024] The continuous glass fiber fabric was dried at 110°C for 3 hours to remove surface-adsorbed moisture. A 1.0% (w / w) hydrolysate of 3-glycidyl etheroxypropyltrimethoxysilane was prepared, with an ethanol to water mass ratio of 95:5. The pH was adjusted to 4.5 with acetic acid, and hydrolysis was carried out at room temperature for 30 minutes. The dried glass fiber fabric was completely immersed in the hydrolysate at a glass fiber to hydrolysate mass ratio of 1:20. After immersion for 20 minutes, the fabric was removed and excess hydrolysate was removed by roller pressing to ensure a uniform liquid content in the fibers. Subsequently, it was pre-dried at 80°C for 30 minutes, and then heated to 110°C in dry nitrogen for 60 minutes to allow the silane to fully condense with the hydroxyl groups on the glass fiber surface, forming an epoxy silane layer linked by silicon-oxygen bonds.

[0025] After the treated fibers cooled to room temperature, the initial amount of reactive epoxy groups (E0) was determined using a hydrochloric acid-acetone ring-opening and potentiometric back titration method. Specifically, a known mass of the sample was reacted with a known excess of hydrochloric acid-acetone solution at 25°C. The remaining acid content was determined using a sodium hydroxide ethanol standard solution. The acid consumption of the fiber itself was subtracted from the amount of unsilanized fiber used as a blank. The result was then converted to the amount of reactive epoxy group material per gram of initially dried glass fiber, expressed in mmol / g. In this example, E0 was measured to be 0.42 mmol / g.

[0026] Based on the target first-stage epoxy apparent conversion rate xH=0.18, corresponding to 1.5 times the amount of epoxy moles consumed, the molar amount of bis(2-hydroxyethyl) disulfide was calculated. The reaction was carried out under nitrogen protection at 75°C for 4 hours. After the reaction, the fibers were thoroughly washed with anhydrous ethanol until no free bis(2-hydroxyethyl) disulfide was detected in the washing solution. After vacuum drying, the remaining epoxy amount E1 was determined using the same method as described above. Based on the target conversion rate, the theoretical control value of E1 is approximately 0.344 mmol / g. In actual production, the E1 measured using the same method is used as the control basis, and fluctuations within the preset detection error range are allowed.

[0027] Subsequently, based on the target second-stage epoxy apparent conversion rate xP=0.10, corresponding to 1.5 times the molar amount of epoxy groups consumed, the feed amount of polycaprolactone diol with a number average molecular weight of approximately 1500 g / mol was calculated. Simultaneously, 0.2% (by mass) of 1-methylimidazole was added as an epoxy ring-opening catalyst. The reaction was carried out under nitrogen protection at 95°C for 8 hours. After the reaction, the mixture was washed with ethyl acetate to constant weight, vacuum dried, and the remaining epoxy group content (E2) was measured. Based on the target conversion rate, the theoretical control value of E2 is approximately 0.302 mmol / g. In actual production, the E2 measured using the same method was used as the control basis. The catalyst was removed after thorough washing and vacuum drying to prevent residual catalyst from affecting the subsequent polyurethane curing reaction.

[0028] The amount of hydroxyl groups that can participate in the reaction at the interface was determined using a monoisocyanate probe method. The dried fibers were reacted with a known excess of phenyl isocyanate in an anhydrous medium. The remaining isocyanate amount was determined by di-n-butylamine back titration, and the blank value of epoxy-based silane fibers untreated with bis(2-hydroxyethyl) disulfide and polycaprolactone diol was subtracted. This measured value was used for subsequent OHt calculations and cannot be directly estimated based on the amount of epoxy groups consumed.

[0029] Preparation of isocyanate-terminated polyurethane prepolymer: Polypropylene glycol (number average molecular weight of about 2000 g / mol) and isophorone diisocyanate were mixed at a molar ratio of isocyanate group to hydroxyl group of about 2.2:1. The mixture was reacted at 80~90℃ with dibutyltin dilaurate as catalyst. The NCO content was measured to be about 6.5% by di-n-butylamine back titration.

[0030] Preparation of the matrix polyol: Polypropylene glycol (number average molecular weight approximately 2000 g / mol) and trifunctional polypropylene glycol (number average molecular weight approximately 3000 g / mol) were mixed at a mass ratio of 9:1. The NCO content of the prepolymer, the hydroxyl value of the matrix polyol, and the amount of hydroxyl groups that can participate in the reaction at the above interfaces were determined separately, and the mixture was prepared according to NCOt / OHt = 1.06. The total hydroxyl equivalent OHt is the sum of the amount of hydroxyl substances in the matrix polyol and the amount of hydroxyl substances that can participate in the reaction at the interface as measured by the monoisocyanate probe method; the total isocyanate equivalent NCOt is the amount of isocyanate groups added to the solvent-free polyurethane reaction system. Except for the bis(2-hydroxyethyl) disulfide pre-covalently anchored to the epoxy silane layer, no free bis(2-hydroxyethyl) disulfide or other disulfide-bonded diols were added.

[0031] Based on 100 parts by mass of initially dried glass fiber, when the target inorganic fiber mass fraction is 55%, the total mass of the polyurethane reactant is 81.82 parts by mass; the mass of the interface anchor is included in the total mass of the composite material according to the actual grafting amount. The reactants are mixed and degassed at 70°C, and the treated glass fiber fabric is impregnated at 70°C, cured at 95°C for 4 hours, and then cured at 110°C for 2 hours.

[0032] After curing, the resulting composite material was heated and pressurized at 145°C and 3MPa for 15 minutes, and then cooled to no higher than 60°C under the condition of maintaining external pressure constraint before depressurization, thus obtaining the solvent-free polyurethane fiber composite material of this embodiment.

[0033] By characterizing the fiber surface at each stage of treatment, such as Figure 2 As shown, unmodified glass fiber at approximately 1100 wavenumbers / cm -1 A broad absorption peak is observed at approximately 3400 wavenumbers / cm², representing the silicon-oxygen framework. -1 A broad hydroxyl peak is observed at the surface for adsorbed water; after the formation of the epoxy silane layer, a wavenumber of approximately 910 / cm² is observed. -1 A distinct characteristic absorption peak of epoxy groups appears at approximately 2930 wavenumbers / cm². -1 A peak of methylene stretching vibration of silanepropyl group appears at [location missing]. After anchoring with bis(2-hydroxyethyl) disulfide and thorough washing, [wavenumber missing] is approximately 910 / cm. -1 The characteristic peak of the epoxy group at that location was significantly attenuated, while the wavenumber was approximately 3400 / cm. -1 The enhanced absorption peak at the hydroxyl group indicates that some epoxy groups have undergone ring-opening reaction and introduced hydroxyl groups. After anchoring with polycaprolactone diol and thorough washing, the absorption peak was approximately 910 wavenumbers / cm. -1 The characteristic peak of residual epoxy groups further weakens to near baseline levels, while at approximately 1730 wavenumbers / cm²... -1 A distinct absorption peak for the ester carbonyl group appears at approximately 3400 wavenumbers / cm. -1 The further broadening and enhancement of the hydroxyl absorption peak indicates that polycaprolactone diol has been covalently linked to the surface of the silane layer and retains terminal hydroxyl groups available for subsequent reactions. Figure 3 As shown, the XPS S2p high-resolution spectrum of the epoxy silane layer showed no obvious photoelectron signal in the binding energy range of 163–160 eV; however, after anchoring with bis(2-hydroxyethyl) disulfide and thorough washing, an S2p region at approximately 163.5 eV appeared. 3 / 2 The peak and the S2p peak at approximately 164.7 electron volts. 1 / 2The peaks, with spin orbital splitting of approximately 1.2 electron volts and an area ratio of approximately 2:1, are consistent with the chemical state characteristics of sulfur in disulfide bonds, confirming that sulfur-containing molecules are covalently fixed to the fiber surface rather than physically adsorbed. This demonstrates that the stepwise anchoring process can covalently link two types of functional molecules to the interfacial region adjacent to the fiber.

[0034] Example 2 This embodiment provides a solvent-free polyurethane fiber composite material and its preparation method. The specific steps of the method are as follows.

[0035] Glass fiber chopped strand mat (chopped fiber length 10~30mm) was dried at 110℃ for 3h. A 1.0% (w / w) 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate was prepared, with an ethanol to water mass ratio of 95:5 and pH 4.5, and hydrolyzed for 30min. The fiber to hydrolysate mass ratio was 1:20, and the mixture was impregnated for 20min, then rolled to remove the liquid, pre-dried at 80℃ for 30min, and treated at 110℃ for 60min in dry nitrogen. After determining E0 to be 0.40 mmol / g, bis(2-hydroxyethyl) disulfide was added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xH=0.10. The reaction was carried out at 75°C for 4 h under nitrogen, and washed with anhydrous ethanol until no free bis(2-hydroxyethyl) disulfide was detected in the washings. After vacuum drying, E1 was measured. Polycaprolactone diol with a number average molecular weight of approximately 1000 g / mol and 0.2% (by mass) of 1-methylimidazole were added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xP=0.05. The reaction was carried out at 95°C for 8 h under nitrogen, washed with ethyl acetate to constant weight, and after vacuum drying, E2 was measured. The amount of hydroxyl groups that could participate in the reaction at the interface was determined using a monoisocyanate probe method.

[0036] The isocyanate-terminated polyurethane prepolymer was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and isophorone diisocyanate at an NCO:OH molar ratio of approximately 2.2:1, with an actual NCO content of approximately 6.5%. The matrix polyol was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and trifunctional polypropylene glycol (number average molecular weight approximately 3000 g / mol) at a mass ratio of 9:1. The mixture was prepared with an NCOt / OHt ratio of 1.02, where OHt is the sum of the hydroxyl equivalents of the matrix polyol and the interfacial reactive hydroxyl equivalents. Based on 100 parts by mass of initially dried fiber, the resin feed amount was calculated based on a final fiber mass fraction of 55%. The reaction components were mixed and degassed at 70°C, the treated fibers were impregnated at 70°C, cured at 95°C for 4 hours, and then cured again at 110°C for 2 hours. The resulting composite material was heated and pressurized at 130℃ and 1MPa for 30 minutes, and then cooled to no higher than 60℃ while maintaining external pressure constraint before depressurization.

[0037] Example 3 This embodiment provides a solvent-free polyurethane fiber composite material and its preparation method. The specific steps of the method are as follows.

[0038] Basalt fiber unidirectional fiber layup was dried at 110℃ for 3 hours. A 1.0% (w / w) 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate was prepared with an ethanol to water mass ratio of 95:5 and a pH of 4.5, and hydrolyzed for 30 minutes. The fiber to hydrolysate mass ratio was 1:20, and the fiber was impregnated for 20 minutes, then rolled to remove the liquid, pre-dried at 80℃ for 30 minutes, and treated at 110℃ for 60 minutes in dry nitrogen. After determining E0 to be 0.45 mmol / g, bis(2-hydroxyethyl) disulfide was added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xH=0.25. The reaction was carried out at 75°C for 4 h under nitrogen, washed with anhydrous ethanol until no free bis(2-hydroxyethyl) disulfide was detected, and then dried under vacuum before measuring E1. Polycaprolactone diol with a number average molecular weight of approximately 2000 g / mol and 0.2% (by mass) of 1-methylimidazole were added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xP=0.15. The reaction was carried out at 95°C for 8 h under nitrogen, washed with ethyl acetate to constant weight, and then dried under vacuum before measuring E2. The amount of hydroxyl groups that could participate in the reaction at the interface was determined using a monoisocyanate probe method.

[0039] The isocyanate-terminated polyurethane prepolymer was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and isophorone diisocyanate at an NCO:OH molar ratio of approximately 2.2:1, with an actual NCO content of approximately 6.5%. The matrix polyol was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and trifunctional polypropylene glycol (number average molecular weight approximately 3000 g / mol) at a mass ratio of 9:1. The mixture was prepared with an NCOt / OHt ratio of 1.10, where OHt is the sum of the hydroxyl equivalents of the matrix polyol and the interfacial reactive hydroxyl equivalents. Based on 100 parts by mass of initially dried fiber, the resin feed amount was calculated based on a final fiber mass fraction of 55%. The reaction components were mixed and degassed at 70°C, the treated fibers were impregnated at 70°C, cured at 95°C for 4 hours, and then cured again at 110°C for 2 hours. The resulting composite material was heated and pressurized at 160℃ and 5MPa for 5 minutes, and then cooled to no higher than 60℃ while maintaining external pressure constraints before depressurization.

[0040] Example 4 This embodiment provides a solvent-free polyurethane fiber composite material and its preparation method. The specific steps of the method are as follows.

[0041] The continuous glass fiber fabric was dried at 105℃ for 4 hours. A 0.5% (w / w) hydrolysate of 3-glycidyl etheroxypropyltrimethoxysilane was prepared, with an ethanol to water ratio of 95:5. The pH was adjusted to 4.0 with acetic acid, and the hydrolysate was hydrolyzed for 30 minutes. The fiber to hydrolysate ratio was 1:20. The fiber was impregnated for 20 minutes, then rolled to remove the liquid, pre-dried at 80℃ for 30 minutes, and treated at 110℃ for 60 minutes in dry nitrogen. After determining E0 to be 0.38 mmol / g, bis(2-hydroxyethyl) disulfide was added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xH=0.18. The reaction was carried out at 60℃ for 8 h under nitrogen, washed with anhydrous ethanol until no free bis(2-hydroxyethyl) disulfide was detected, and then dried under vacuum before measuring E1. Polycaprolactone diol with a number average molecular weight of approximately 1500 g / mol and tetrabutylammonium bromide (0.5% of the mass of the epoxy silane layer) were added as catalysts at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xP=0.10. The reaction was carried out at 80℃ for 12 h under nitrogen, washed with ethyl acetate to constant weight, and then dried under vacuum before measuring E2. The amount of hydroxyl groups that could participate in the reaction at the interface was determined using a monoisocyanate probe method.

[0042] The isocyanate-terminated polyurethane prepolymer was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and isophorone diisocyanate at an NCO:OH molar ratio of approximately 2.2:1, with an actual NCO content of approximately 6.5%. The matrix polyol was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and trifunctional polypropylene glycol (number average molecular weight approximately 3000 g / mol) at a mass ratio of 9:1. The mixture was prepared with an NCOt / OHt ratio of 1.06, where OHt is the sum of the hydroxyl equivalent of the matrix polyol and the hydroxyl equivalent that can participate in the reaction at the interface. Based on 100 parts by mass of initially dried fiber, the resin feed amount was calculated based on a final fiber mass fraction of 55%. The reaction components were mixed and degassed at 70°C, the treated fibers were impregnated at 60°C, and cured at 80°C for 8 hours. The resulting composite material was heated and pressurized at 145℃ and 3MPa for 15 minutes, and then cooled to no higher than 60℃ while maintaining external pressure constraints before depressurization.

[0043] Example 5 This embodiment provides a solvent-free polyurethane fiber composite material and its preparation method. The specific steps of the method are as follows.

[0044] The continuous glass fiber fabric was dried at 120℃ for 2 hours. A 2.0% (w / w) hydrolysate of 3-glycidyl etheroxypropyltrimethoxysilane was prepared, with an ethanol to water ratio of 95:5. The pH was adjusted to 5.0 with acetic acid, and the hydrolysate was hydrolyzed for 30 minutes. The fiber to hydrolysate ratio was 1:20. The fiber was impregnated for 20 minutes, then rolled to remove the liquid, pre-dried at 80℃ for 30 minutes, and treated at 110℃ for 60 minutes in dry nitrogen. After determining E0 to be 0.48 mmol / g, bis(2-hydroxyethyl) disulfide was added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xH=0.18. The reaction was carried out at 85°C for 2 h under nitrogen, washed with anhydrous ethanol until no free bis(2-hydroxyethyl) disulfide was detected, and then dried under vacuum before measuring E1. Polycaprolactone diol with a number average molecular weight of approximately 1500 g / mol and 0.2% (by mass) of 1-methylimidazole were added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xP=0.10. The reaction was carried out at 110°C for 4 h under nitrogen, washed with ethyl acetate to constant weight, and then dried under vacuum before measuring E2. The amount of hydroxyl groups that could participate in the reaction at the interface was determined using a monoisocyanate probe method.

[0045] The isocyanate-terminated polyurethane prepolymer was prepared from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and isophorone diisocyanate at an NCO:OH molar ratio of approximately 2.2:1, with an actual NCO content of approximately 6.5%. The matrix polyol was mixed from polypropylene glycol (number average molecular weight approximately 2000 g / mol) and trifunctional polypropylene glycol (number average molecular weight approximately 3000 g / mol) at a mass ratio of 9:1. The mixture was prepared with an NCOt / OHt ratio of 1.06, where OHt is the sum of the hydroxyl equivalent of the matrix polyol and the hydroxyl equivalent that can participate in the reaction at the interface. Based on 100 parts by mass of initially dried fiber, the resin feed amount was calculated based on a final fiber mass fraction of 55%. The reaction components were mixed and degassed at 70°C, the treated fibers were impregnated at 80°C, and cured at 110°C for 2 hours. The resulting composite material was heated and pressurized at 145℃ and 3MPa for 15 minutes, and then cooled to no higher than 60℃ while maintaining external pressure constraints before depressurization.

[0046] Comparative Example 1 This comparative example provides a fiber composite material that is anchored only to bis(2-hydroxyethyl) disulfide and not to polycaprolactone diol. The specific steps of this method are as follows.

[0047] The continuous glass fiber fabric was dried at 110°C for 3 hours, and an epoxy silane layer was formed under the same conditions as in Example 1, with an E0 of 0.42 mmol / g. Bis(2-hydroxyethyl) disulfide was added at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xH=0.18. The reaction was carried out at 75°C under nitrogen for 4 hours, followed by washing with anhydrous ethanol until no free bis(2-hydroxyethyl) disulfide was detected. After vacuum drying, E1 was measured. The polycaprolactone diol reaction stage was skipped, and the process proceeded directly to step S3. The remaining prepolymer and matrix polyol formulations, feed ratios, impregnation curing, and hot-pressing conditions were the same as in Example 1.

[0048] Comparative Example 2 This comparative example provides a fiber composite material anchored only to polycaprolactone diol and not to bis(2-hydroxyethyl) disulfide. The specific steps of this method are as follows.

[0049] The continuous glass fiber fabric was dried at 110°C for 3 hours, and an epoxy silane layer was formed under the same conditions as in Example 1, with an E0 of 0.42 mmol / g. Without adding bis(2-hydroxyethyl) disulfide, polycaprolactone diol with a number average molecular weight of approximately 1500 g / mol and 0.2% (by mass) of 1-methylimidazole were added directly at 1.5 times the molar amount of epoxy groups consumed corresponding to the target xP=0.10. The reaction was carried out at 95°C for 8 hours under nitrogen, washed with ethyl acetate to constant weight, and dried under vacuum before measuring E2. The remaining prepolymer and matrix polyol formulations, feed ratios, impregnation curing, and hot-pressing conditions were the same as in Example 1.

[0050] Comparative Example 3 This comparative example provides a fiber composite material in which a free disulfide bond chain extender is introduced into a bulk polyurethane. The specific steps of this method are as follows.

[0051] The epoxy silane layer treatment on the inorganic fiber surface was the same as in Example 1, but only conventional silanization was performed without anchoring bis(2-hydroxyethyl) disulfide and polycaprolactone diol. In step S3, an equivalent mass of bis(2-hydroxyethyl) disulfide as in Example 1 was directly added to the solvent-free polyurethane reaction system as a free chain extender, mixed with the prepolymer and matrix polyol, and then used to impregnate the fiber and cure. The remaining prepolymer and matrix polyol formulations, isocyanate index, curing, and hot-pressing conditions were the same as in Example 1.

[0052] Comparative Example 4 This comparative example provides a fiber composite material without interface modification. The specific steps of this method are as follows.

[0053] The glass fiber continuous fiber fabric was dried at 110°C for 3 hours, without any silane coupling agent treatment, and without anchoring bis(2-hydroxyethyl) disulfide and polycaprolactone diol. It was then directly impregnated, cured, and hot-pressed in the same solvent-free polyurethane reaction system as in Example 1.

[0054] The composite materials prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to performance tests. To verify the synergistic design of interface dynamics and bulk stabilization from a thermomechanical response perspective, dynamic thermomechanical analysis was performed on Example 1 and Comparative Example 3, and constant strain stress relaxation tests were conducted on Example 1, Comparative Example 2, and Comparative Example 3. Figure 4 As shown, the storage modulus E' of Example 1 is approximately 22 GPa at room temperature. A significant primary transition step appears as the temperature rises to approximately 90 °C, corresponding to the glass transition of the soft segments in the main polyurethane matrix. Within the hot-pressing window of 130–160 °C, E' exhibits a secondary decay step of approximately 15%, corresponding to the interfacial relaxation process formed by the synergistic formation of bis(2-hydroxyethyl) disulfide and polycaprolactone diol in the interfacial region. Simultaneously, the loss factor tanδ shows a shoulder peak independent of the primary transition in this temperature range, with a loss factor value of approximately 0.15, demonstrating that the interfacial relaxation behavior is thermomechanically decoupled from the glass transition of the main network, and the interfacial region possesses relatively independent thermal response characteristics. In contrast, Comparative Example 3, due to the uniform introduction of disulfide bonds into the bulk network via a free chain extender, experiences a shift and significant broadening of its primary transition towards lower temperatures. The storage modulus E' is significantly lower throughout the entire test temperature range and collapses sharply above 130 °C, with a modulus decrease exceeding 60%, indicating severe softening of the main network at the hot-pressing temperature. Figure 5 As shown, under constant strain conditions at 145 °C, the normalized stress of Example 1 decayed rapidly in the initial stage, dropping to about 0.60 after 60 minutes, and then entered the plateau region, stabilizing at about 0.35 after 300 minutes. This indicates that after sufficient relaxation and rearrangement of the interfacial chain segments, the main cross-linked network still maintained topological integrity. In Comparative Example 2, because the interface only contained polycaprolactone diol and no dynamic bonds, the stress hardly decayed, and the normalized stress was still higher than 0.85 after 300 minutes. The material maintained an elastomer response, making it difficult to achieve effective permanent reshaping through stress relaxation. In Comparative Example 3, the stress rapidly decayed to close to 0.05 within 30 minutes, and the material underwent viscous fluidization, confirming that the bulk dynamic network had completely lost its load-bearing capacity.

[0055] Flexural strength and flexural modulus were tested according to GB / T 1449, and interlaminar shear strength was tested according to GB / T 1450.1. Five parallel samples were tested in each group, and the results were expressed as mean ± standard deviation.

[0056] Hot-press reshaping performance test: A bending specimen with dimensions of 80mm × 15mm × 2mm was hot-pressed in a mold at 145℃ and 3MPa for 15 minutes. The external pressure was maintained, and the specimen was cooled to a temperature not exceeding 60℃ before being depressurized, shaping the specimen into an L-shape (inner bending angle 90°). After demolding, the specimen was placed in a standard environment (23±2℃, 50±5%RH) for 24 hours. The bending strength and interlaminar shear strength after hot-press reshaping were measured, and the springback Δθ was measured. The shape retention rate was calculated as η = (90° - Δθ) / 90° × 100%.

[0057] Cyclic hot pressing test: The L-shaped specimen was laid flat again and hot-pressed again under the conditions of 145℃, 3MPa, 15min and external pressure constraint cooling. The cycle was repeated 5 times and the bending strength after the 5th cycle was measured.

[0058] The test results are shown in Table 1.

[0059] Table 1 Performance test results of each embodiment and comparative example Note: S1-S5 represent Examples 1-5 respectively, and D1-D4 represent Comparative Examples 1-4 respectively; the hot pressing and reshaping test was uniformly carried out at 145℃, 3MPa, and 15min to eliminate the influence of differences in hot pressing process on transverse comparability; the shape retention rate was calculated based on the angular rebound amount of the L-shaped sample 24h after shaping.

[0060] Compared to Comparative Example 4, the initial flexural strength of Example 1 increased from 258 MPa to 485 MPa, and the initial interlaminar shear strength increased from 15.2 MPa to 38.2 MPa, representing increases of approximately 88% and 151%, respectively. This result indicates that the interfacial bonding between the inorganic fibers and the polyurethane matrix was significantly improved after synergistic modification with an epoxy silane layer and bis(2-hydroxyethyl) disulfide and polycaprolactone diol, resulting in a substantial increase in load transfer efficiency. In Comparative Example 4, the flexural strength retention rate after hot pressing and resetting was only 55.0%, the interlaminar shear retention rate was only 56.6%, and the shape retention rate was only 8.5%. After 5 cycles, the flexural strength retention rate decreased to 32.9%, indicating that the unmodified composite material not only had poor initial performance but also experienced severe delamination and interfacial failure during hot pressing, making it unable to withstand hot pressing and resetting operations.

[0061] Compared to Comparative Example 1, Example 1 exhibits significantly superior interlaminar shear strength and hot-pressing resetting performance. The initial interlaminar shear strength of Comparative Example 1 was 29.5 MPa, lower than the 38.2 MPa of Example 1. This indicates that when only bis(2-hydroxyethyl) disulfide is introduced without polycaprolactone diol, the interface lacks sufficient flexible segments and entanglement effects, resulting in a higher interfacial stress concentration factor and decreased shear force transfer efficiency. In particular, the flexural strength retention rate of Comparative Example 1 after hot-pressing resetting was only 77.4%, the shape retention rate was only 68.5%, and the flexural strength retention rate after 5 cycles was only 61.4%, all significantly lower than the corresponding indicators of Example 1. This data shows that although bis(2-hydroxyethyl) disulfide provides dynamic covalent bond exchange capability, without the synergistic effect of the flexible long chains of polycaprolactone diol, the interfacial region lacks sufficient segment mobility during hot pressing, resulting in insufficient stress relaxation. Dynamic bond exchange is accompanied by the initiation of microcracks and interfacial defects, leading to a continuous decline in mechanical properties during cyclic hot pressing. This indicates that the introduction of polycaprolactone diol helps to provide space for interfacial chain segment movement, promotes uniform stress relaxation, and thus maintains the integrity of the interfacial structure during dynamic bond exchange.

[0062] Compared to Comparative Example 2, Example 1 showed a fundamental difference in shape retention. The initial flexural strength of Comparative Example 2 was 405 MPa, and after hot pressing and reshaping, it was 388 MPa, corresponding to a strength retention rate as high as 95.8%. After 5 cycles, the retention rate was still 86.9%, superficially close to that of Example 1. However, the shape retention rate of Comparative Example 2 was only 26.3%, far lower than the 93.5% of Example 1. This result indicates that although the introduction of polycaprolactone diol improved the interfacial flexibility and physical entanglement of Comparative Example 2, resulting in no significant strength loss after a single hot pressing, the lack of disulfide dynamic covalent bonds meant that its hot pressing process mainly relied on the untangling and rearrangement of physical entanglement. This physical mechanism is highly reversible, resulting in significant elastic rebound after demolding, and permanent shape retention cannot be achieved through chemical structural rearrangement. Simultaneously, the interlaminar shear retention rate of Comparative Example 2 (85.1%) was lower than that of Example 1 (91.9%), indicating that under hot pressing shear stress, only the physically entangled interfaces experienced significant slippage. Therefore, Comparative Example 2 does not possess the hot-press reshaping capability described in this invention, and the introduction of bis(2-hydroxyethyl) disulfide is necessary to achieve permanent shape reconstruction.

[0063] Compared to Comparative Example 3, Example 1 demonstrates the core advantage of the synergistic design of interface dynamism and matrix stabilization in this invention. Comparative Example 3 uniformly introduces disulfide bonds into the bulk polyurethane network using a free chain extender, resulting in an initial flexural modulus of only 18.5 GPa, lower than the 22.4 GPa of Example 1. This indicates that the soft segment dynamic structure introduced into the bulk reduces the matrix rigidity. After hot pressing and resetting, Comparative Example 3 exhibits a flexural strength retention rate of only 64.7%, an interlaminar shear retention rate of only 57.8%, and a shape retention rate of only 55.2%. After five cycles, the flexural strength retention rate further decreases to 43.8%, a significantly higher attenuation rate than Example 1. This data indicates that when disulfide bonds are uniformly distributed in the bulk network, the entire polyurethane matrix participates in dynamic rearrangement under hot pressing temperatures, leading to the destruction of the crosslinked network integrity, a sharp decline in the matrix's load-bearing capacity, and the inability to maintain interfacial force transmission stability. In contrast, Example 1 strictly confines the bis(2-hydroxyethyl) disulfide to the interfacial region adjacent to the fiber, and the main polyurethane matrix does not contain free disulfide chain extenders, which helps to reduce the dynamic rearrangement of the bulk network during hot pressing, thereby achieving interface reshaping while maintaining the load-bearing capacity of the main body.

[0064] The comparison between Examples 1-5 reveals the influence of process parameters on the properties of composite materials. Example 2 uses chopped fiber mat morphology and reduces xH and xP values. Its initial flexural strength is 450 MPa and initial interlaminar shear strength is 34.8 MPa, both lower than Example 1. The shape retention rate is 88.4%, and the retention rate after 5 cycles is 85.6%, indicating that the lower interfacial dynamic bond density and flexible segment density have a certain impact on the hot pressing resetting effect, but the flexural modulus is well maintained. Example 3 uses basalt fiber unidirectional layup and increases the xH, xP values ​​and polycaprolactone diol molecular weight, obtaining the highest initial flexural strength (510 MPa) and interlaminar shear strength (40.5 MPa). The retention rates after hot pressing resetting are 95.7% and 93.3%, respectively, and the retention rate after 5 cycles is 91.8%, indicating that increasing the interfacial dynamic bond density and flexible segment length is beneficial to enhancing interfacial load transfer and shaping stability. Examples 4 and 5 are located at the low-temperature and high-temperature boundaries of the process parameter range, respectively, and their various properties are between those of Example 1 and Example 2 or Example 3, which verifies the rationality of the process parameter range of the present invention.

[0065] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A solvent-free polyurethane fiber composite material, characterized in that: The solvent-free polyurethane fiber composite material includes inorganic fibers, an epoxy silane layer formed on the surface of the inorganic fibers, and a polyurethane matrix formed using a solvent-free polyurethane reaction system; The epoxy silane layer includes a first ring-opening linking group and a second ring-opening linking group formed by ring-opening different epoxy groups respectively. Bis(2-hydroxyethyl) disulfide is covalently linked to the epoxy silane layer through the first ring-opening linking group, and polycaprolactone diol is covalently linked to the epoxy silane layer through the second ring-opening linking group. The hydroxyl groups of the bis(2-hydroxyethyl) disulfide and the polycaprolactone diol, after anchoring, can react with the isocyanate groups in the solvent-free polyurethane reaction system to form urethane bonds, thereby covalently linking the epoxy silane layer to the polyurethane matrix. Except for the bis(2-hydroxyethyl) disulfide pre-covalently anchored to the epoxy silane layer, the solvent-free polyurethane reaction system does not contain free disulfide chain extenders and disulfide crosslinking agents.

2. The solvent-free polyurethane fiber composite material according to claim 1, characterized in that: The inorganic fiber is glass fiber or basalt fiber, and the inorganic fiber is in the form of chopped fiber mat, continuous fiber fabric or unidirectional fiber layup.

3. The solvent-free polyurethane fiber composite material according to claim 1, characterized in that: The epoxy silane layer is formed by the hydrolysis of 3-glycidyl etheroxypropyltrimethoxysilane and its condensation with hydroxyl groups on the surface of the inorganic fiber.

4. The solvent-free polyurethane fiber composite material according to claim 1, characterized in that: The number average molecular weight of the polycaprolactone diol is 1000-2000 g / mol, and the inorganic fiber accounts for 45%-65% of the mass fraction of the solvent-free polyurethane fiber composite material.

5. A method for preparing a solvent-free polyurethane fiber composite material as described in any one of claims 1-4, characterized in that: The method includes the following steps: S1. Dry the inorganic fiber to form an epoxy silane layer on its surface, and measure the initial amount of reactive epoxy groups E0 based on the initial mass of the initially dried inorganic fiber. S2. React bis(2-hydroxyethyl) disulfide with some of the epoxy groups to remove unreacted bis(2-hydroxyethyl) disulfide and measure the remaining epoxy group amount E1; then react polycaprolactone diol with some of the epoxy groups that have not yet reacted after the first stage to remove unreacted polycaprolactone diol and measure the remaining epoxy group amount E2. E0, E1 and E2 are determined using the same method and expressed according to the same mass standard. S3. The inorganic fibers treated in step S2 are brought into contact with a solvent-free polyurethane reaction system containing isocyanate-terminated polyurethane prepolymer and matrix polyol, so that the hydroxyl groups of the matrix polyol and the hydroxyl groups that can participate in the reaction at the interface react with the isocyanate groups to form a polyurethane matrix covalently linked to the epoxy silane layer; except for the pre-anchored bis(2-hydroxyethyl) disulfide, no free disulfide chain extender and disulfide crosslinker are added to the solvent-free polyurethane reaction system.

6. The method for preparing a solvent-free polyurethane fiber composite material according to claim 5, characterized in that: In step S1, the inorganic fibers are dried at 105-120℃ for 2-4 hours; the inorganic fibers are treated with a 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate with a mass fraction of 0.5%-2.0% and a pH of 4.0-5.0, and after removing excess hydrolysate, they are pre-dried and heat-cured.

7. The method for preparing a solvent-free polyurethane fiber composite material according to claim 5, characterized in that: In step S2, the apparent conversion rate of the epoxy groups in the first stage, calculated according to formula xH=(E0-E1) / E0, is 0.10-0.25 after the reaction of bis(2-hydroxyethyl) disulfide with epoxy groups until the reaction is completed; the apparent conversion rate of the epoxy groups in the second stage, calculated according to formula xP=(E1-E2) / E0, is 0.05-0.15 after the reaction of polycaprolactone diol with the unreacted epoxy groups after the first stage.

8. The method for preparing a solvent-free polyurethane fiber composite material according to claim 5, characterized in that: In step S2, bis(2-hydroxyethyl) disulfide is reacted in a dry, inert atmosphere at 60-85°C for 2-8 hours; polycaprolactone diol is reacted in a dry, inert atmosphere at 80-110°C for 4-12 hours; at least one reaction stage is carried out in the presence of an epoxy ring-opening catalyst, wherein the epoxy ring-opening catalyst is 1-methylimidazolium or tetrabutylammonium bromide.

9. The method for preparing a solvent-free polyurethane fiber composite material according to claim 5, characterized in that: In step S3, the total hydroxyl equivalent OHt is the sum of the hydroxyl equivalent of the matrix polyol and the measured interfacial hydroxyl equivalent that can participate in the reaction, the total isocyanate equivalent is NCOt, and the NCOt / OHt ratio is 1.02-1.10; the inorganic fiber and the solvent-free polyurethane reaction system are impregnated at 60-80℃ and cured at 80-110℃ for 2-8 hours.

10. The method for preparing a solvent-free polyurethane fiber composite material according to claim 5, characterized in that: After the polyurethane matrix is ​​formed and cured in step S3, the resulting solvent-free polyurethane fiber composite material is heated and pressurized at 130-160℃ and 1-5MPa for 5-30 minutes, and then cooled to no higher than 60℃ under the condition of maintaining external pressure constraint before depressurization.